An open trial of risperidone in the treatment of schizophrenia in the University of Malaya Medical Centre - Jambunathan, S.T.; Aili, H.H. (2001)
To apalyze the pattern of use and outcome of patients with Schizophreniatreated with Risperidone over a minimum period of one year In an open labellongitudinal descriptive study.